2016
DOI: 10.1089/can.2016.0029
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Users' Recommended Warnings for Packages of Legally Sold Cannabis: An Australia-Centered Study

Abstract: Introduction: Although cannabis use creates health risks, governments have recently been legalizing either medical use or leisure use. These governments can mandate health warnings on cannabis packages. Prior research examined recommended warnings of cannabis experts. The aim of this study was to obtain suggested cannabis health and safety warnings from cannabis users.Methods: We used a media release, Facebook postings, and announcements in university classes to seek individuals who had used cannabis at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…Only Canada has warnings about the risk of harm to mental health. No government mandates graphic warnings, which are becoming common with regards to tobacco packages (Bekalu et al 2019 ), and no government mandates providing a quit-line phone number, as suggested by recreational users of cannabis in a prior study (Malouff et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only Canada has warnings about the risk of harm to mental health. No government mandates graphic warnings, which are becoming common with regards to tobacco packages (Bekalu et al 2019 ), and no government mandates providing a quit-line phone number, as suggested by recreational users of cannabis in a prior study (Malouff et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Canada mandates all nine types of warnings listed in the table a Malouff et al, 2013 . b Malouff et al ( 2016 )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their subsequent work, 22 these categories included mental health risks, machinery operational risks, short-term and long-term physical problems, reasonable use, and dependency, addiction, and abuse.…”
mentioning
confidence: 99%